2020
DOI: 10.1101/2020.12.08.413955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A connectome of theDrosophilacentral complex reveals network motifs suitable for flexible navigation and context-dependent action selection

Abstract: Flexible behaviors over long timescales are thought to engage recurrent neural networks in deep brain regions, which are experimentally challenging to study. In insects, recurrent circuit dynamics in a brain region called the central complex (CX) enable directed locomotion, sleep, and context- and experience-dependent spatial navigation. We describe the first complete electron-microscopy-based connectome of the Drosophila CX, including all its neurons and circuits at synaptic resolution. We identified new CX n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
138
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(155 citation statements)
references
References 461 publications
(1,339 reference statements)
16
138
1
Order By: Relevance
“…In this framework, PFR and hΔB cells develop tuning to the fly’s allocentric traveling direction because neurons at an intermediate processing layer, the PFNs––which show allocentric heading responses that are multiplicatively scaled by the fly’s egocentric translation direction––perform a coordinate transform. Thus, our data provide a biologically validated example of how neurons with mixed selectivity , i.e., tuned responses to a primary stimulus axis that are further scaled by a second relevant dimension, function to implement a coordinate transformation, lending credence to the computational ideas from parietal cortex 1,4,5 and similar proposals in animal navigation 3436 .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this framework, PFR and hΔB cells develop tuning to the fly’s allocentric traveling direction because neurons at an intermediate processing layer, the PFNs––which show allocentric heading responses that are multiplicatively scaled by the fly’s egocentric translation direction––perform a coordinate transform. Thus, our data provide a biologically validated example of how neurons with mixed selectivity , i.e., tuned responses to a primary stimulus axis that are further scaled by a second relevant dimension, function to implement a coordinate transformation, lending credence to the computational ideas from parietal cortex 1,4,5 and similar proposals in animal navigation 3436 .…”
Section: Discussionsupporting
confidence: 61%
“…Each vector is explicitly represented by a sinusoidal pattern of activity across a defined population of neurons. Characterizing a neuronal circuit for vector arithmetic and reference-frame transformation is a fundamental advance for cognitive neuroscience 3436 .…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral studies in ants (Wehner and Müller, 2006) and dung beetles (el Jundi et al, 2015) have demonstrated that skylight polarization cues can have a greater influence than other visual features in guidance and navigation behaviors. In Drosophila, intensity gradients have been shown to have a greater behavioral significance than polarization (Warren et al, 2018), yet recent connectome analysis of the Drosophila CX highlights the polarization-sensitive ring neurons that we identified here as potentially being at the top of a hierarchy of sensory 17/57 inputs (Hulse et al, 2020). Furthermore, the unique pattern of asymmetrical connectivity between the ER4m populations from each brain hemisphere and the E-PG network hints at an attractively simple system for obtaining 360° heading information from ambiguous 0/180° polarization cues, by using signals from one population or the other depending on which side of the animal the sun is on (Hulse et al, 2020) In vivo calcium imaging…”
Section: /57mentioning
confidence: 79%
“…It has not been demonstrated in fully immobilized animals, hence we did not expect to see it here. Inputs to E-PG neurons from polarization sensitive ER4m (or indeed ER2) neurons also represent only a fraction of the sensory input to the network (Hulse et al, 2020). Nevertheless, we hypothesized that E-PG activity could be modulated by a varying angle of polarized light since the same has been demonstrated in numerous columnar central complex neurons in other insects while immobilized (Heinze and Homberg, 2007;Honkanen et al, 2019).…”
Section: E-pg Organization and Pairings In The Pbmentioning
confidence: 97%
“…Other typing efforts are reported in detail elsewhere (see e.g. (Li et al, 2020) for Kenyon cells, KCs; mushroom body output neurons, MBONs; dopaminergic neurons, DANs; (Hulse et al, 2020) for neurons of the central complex; CXN) (Figure 2A,B). All cell type annotations agreed upon by this consortium have already been made available through the hemibrain v1.1 data release at neuprint.janelia.org in May 2020 (Scheffer et al, 2020; Clements et al, 2020).…”
Section: Resultsmentioning
confidence: 99%